К вопросу о методике подготовки студентов педагогического вуза к духовно-нравственному воспитанию младших школьников - Пархоменко, И.А. (My University, 2016)
The article methods of forming a professional-personal position of students as a basis for improving the quality of their preparation for the spiritual and moral education in primary schools are describes
Keywords: spiritually and moral education; professional-personal position; student; the younger schoolboy